International and Indonesia's Teacher Performance : A Bibliometric Study Based on Vosviewer - Rais Hidayat; Yuyun Elizabeth Patras; Tustiyana Windiyani; Yusuf Gunawan (Universitas Pendidikan Mandalika (UNDIKMA), 2023)
This study aims to analyze teacher performance from various perspectives, including a general description of teacher performance publications; trends; country; organization; source; authors, and the relationship between authors; and teacher performance research hotspots, both in international and Indonesian contexts. This study used the literature review method with data analysis using Vosviewer software. Scientific publication data comes from Scopus in 2003 – 2022 or the last 20 years as many as 393 documents. The findings of this study include the following: the publication of teacher performance in Scopus is still wide open; in the international context, the United States dominates the number of documents, citations, and sources; Indonesia ranks second after the United States even though it loses in the number of citations and links; new hotspots for developing research and publications on teacher performance include: decision support system, covid, attitude, values, authentic leadership, emotional intelligence, educative teacher performance, work discipline, job satisfaction, professional development activity, work motivation, compensation, educational reform, student achievement grade. This study is a source of decision-making for educational organization managers related to teacher performance research and development.